Camera realignment imposes a cost on laparoscopic performance - Christopher L. Hewitson (Nature Portfolio, 2021)
Abstract There is an unresolved question about whether realigned visual feedback is beneficial or costly to laparoscopic task performance. We provide evidence that camera realignment imposes a reliable cost on performance across both naive controls and experienced surgeons. This finding clarifies an important ongoing discussion in the literature about the effects of camera realignment, which could inform the strategies that laparoscopic surgeons use in the operating room.